2016
DOI: 10.1063/1.4961474
|View full text |Cite
|
Sign up to set email alerts
|

Development of a tilt-positioning mechanism driven by flextensional piezoelectric actuators

Abstract: Tilt-positioning mechanisms are required in optical systems for diverse applications. Compared to electromagnetic tilt-positioning mechanisms, piezoelectric tilters are superior with regard to high positioning resolution, cost-effectiveness, and no electromagnetic interference issues. But their applications are limited by small motion ranges. To overcome this problem, a novel piezoelectric tilt-positioning mechanism is proposed and developed in this paper, aiming to achieve a large output range in compact size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Figure 4 a shows the relationship between the rhombus-type compliant mechanism’s amplification ratio and the bridge arm angle when the FEM results are compared with the MSTMM results. The figure shows that the two methods have similar trends, in that the amplification ratio increases initially and subsequently decreases with increasing bridge arm angle, which is consistent with the previous description in the literature [ 52 ]. Furthermore, the relative error between the two models decreases sharply as the angle increases, before gradually stabilizing after 15 .…”
Section: Static Characteristic Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…Figure 4 a shows the relationship between the rhombus-type compliant mechanism’s amplification ratio and the bridge arm angle when the FEM results are compared with the MSTMM results. The figure shows that the two methods have similar trends, in that the amplification ratio increases initially and subsequently decreases with increasing bridge arm angle, which is consistent with the previous description in the literature [ 52 ]. Furthermore, the relative error between the two models decreases sharply as the angle increases, before gradually stabilizing after 15 .…”
Section: Static Characteristic Analysissupporting
confidence: 89%
“…Through a combination of analysis and comparison, it was found that the main cause of this phenomenon is the stress concentration effect in the connection area between the bridge arm of the compliant-amplifying mechanism and the rigid body unit (see Figure 9 a), which results in uneven distribution of the deformation [ 32 , 52 ]. In addition, this error also occurs because the FEM results that are used as reference values will be affected by the quality and size of the mesh.…”
Section: Hybrid Compliance Improvement Modelmentioning
confidence: 99%
“…Figure 4a shows the relationship between the rhombus-type compliant mechanism's amplification ratio and the bridge arm angle when the FEM results are compared with the MSTMM results. The figure shows that the two methods have similar trends, in that the amplification ratio increases initially and subsequently decreases with increasing bridge arm angle, which is consistent with the previous description in the literature [52]. Furthermore, the relative error between the two models decreases sharply as the angle increases, before gradually stabilizing after 15 • .…”
Section: ) Flexible Unitsupporting
confidence: 88%
“…In addition, AV J 0 (φ P ZT ) cos(φ L1 (nT S )) and AV J 0 (φ P ZT ) cos(φ L2 (nT S )) can also be expanded in series of Bessel functions of the first kind. Thus, taking into account (28) and (29), results:…”
Section: Proposed Methodsmentioning
confidence: 99%
“…MAFPAs consist of multi-flexible structures actuated by two or more piezoceramics, and thus, can provide more than one degree of freedom. This solution allows, for example, the development of nanopositioner XY stages [28], tilt-positioning mechanisms [29], piezoelectric grippers [30] and piezoelectric motors [31]. The MAFPA devices used in this paper were designed (using the topology optimization method) and manufactured utilizing two PZT piezoceramics, and therefore actuators with two degrees of freedom were obtained.…”
Section: Transducersmentioning
confidence: 99%